Practical digital geometric morphometric approach for classifying sexual dimorphism of Malaysian adult mandibles using two-dimensional digital images - Tan, Lii Jye; Chai, Tong-Yuen; Koh, Cai Ping; Shafee, Mohamed Swarhib; Hiu, Jessie; Lai, Shau-Kong; Mohd Nor, Faridah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: Assessment of the human mandible has been a component of biological identification in forensic anthropological practice. We employed the digital geometric morphometric analysis, a statistical analysis using Cartesian landmark coordinates for this assessment. In this report, the proposed geometric morphometric approaches have been structured into systematic steps to study the sexual dimorphism of the mandible from two-dimensional (2-D) digital images. Based on the newly developed imaging technique, the variation of mandible size and shape is compared between males and females. Furthermore, the allometry patterns of the mandible could be visualized. Materials and methods: A total of 113 human adult mandibles (65 males, 48 females) were sampled. Twelve selected significant landmarks were plotted on the 2-D image by landmarking software and subsequently subjected to MorphoJ analysis. Results: The initial five principal components accounted for a substantial morphological variance, representing 84.2% of the cumulative variance in the overall dataset (PC1 27.0%, PC2 22.5%, PC3 20.9%, PC4 7.9%, PC5 5.9%). The variance visualization showed a significant difference between the mandible shape of males and females with classification accuracy of 92.0% and cross validation accuracy of 85.7%. Conclusion: This study provides compelling evidence that digital geometric morphometric analysis can serve as an alternative or complementary method for studying sexual dimorphism in the human mandible.